1998
DOI: 10.1080/02841859809172176
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound in the subclavian steal syndrome

Abstract: A complete vertebral steal at US correlated well with subclavian occlusion and a partial steal suggested stenosis of the subclavian artery. There were also flow changes in the contralateral vertebral artery and the common carotid arteries that compensated for the steal. Retrograde vertebral flow at US was sometimes associated with vertebral occlusion in subclavian stenosis without a true subclavian steal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
(6 reference statements)
0
6
1
Order By: Relevance
“…12,13 This was observed in our study in all cases with subclavian thrombosis in this area. In cases with incomplete occlusion of the subclavian artery, Doppler sonography can show reversal of flow during reactive hyperemia or inversion of the systole and forward diastole, 12,14 but in our study we detected only complete occlusions.…”
contrasting
confidence: 70%
“…12,13 This was observed in our study in all cases with subclavian thrombosis in this area. In cases with incomplete occlusion of the subclavian artery, Doppler sonography can show reversal of flow during reactive hyperemia or inversion of the systole and forward diastole, 12,14 but in our study we detected only complete occlusions.…”
contrasting
confidence: 70%
“…A review of literature shows that a complete reversal flow occurs not only in subclavian artery occlusions but also in 6% to 16% of angiographically stenotic subclavian arteries, and that an alternating waveform or systolic deceleration occurs in 17% to 20% of occluded subclavian arteries. 8,21 Furthermore, only a moderate correlation between the worsening waveform type and the degree of subclavian artery stenosis exists, with correlation coefficients ranging from 0.5 to 0.7. 22,23 The present study revealed a significantly greater side-toside difference in brachial arterial blood pressure in the presence of a reversed or an alternating flow compared to mere systolic deceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, retrograde blood flow in the vertebral artery was associated with a significantly higher flow in the contralateral common carotid and vertebral arteries in order to compensate for the central nervous system ischemia. Retrograde flow was increased in cases with complete steal than those with partial steal [16]. Moreover, it has been estimated that more than 90% of patients have at least intermittent flow reversal in the vertebral artery if there is more than 50% stenosis in the proximal portion of the subclavian artery [2].…”
Section: Duplex Ultrasoundmentioning
confidence: 99%